Reshaping Teaching for Sustainability in Business Engineering – A Pilot Study on Students' Outlooks and Learning Expectations - Fleacă, Bogdan; Fleacă, Elena; Corocăescu, Mihai (European Journal of Sustainable Development, 2022)
In the context of the rapid pace of technological advance, increasing technological interconnection and the shift toward sustainable economies, education is required to provide graduates with knowledge and skills to address the complex challenges posed by the fast-moving, globalized and interconnected world. Engineering education has gained particular importance, going beyond the technical knowledge and preparing students for entrepreneurial actions through the acquisition of hands-on, operative capabilities to drive new business models, integrating complex issues of technological change and digitization, environmental and socio-economic concerns. The authors have undertaken a quantitative survey aiming at investigating the students’ outlook on modern sustainable development concerns and collecting relevant learning needs in a wide range of sustainability-related directions. The survey results stressed improvement solutions to augment teaching for sustainability in the case of business engineering areas such as a) embedding interdisciplinary topics into existing curricula linked to SDGs instead of creating new disciplines; b) developing and leveraging core shared values of citizenship for further learning across the entire curriculum and emphasizing the interrelatedness of knowledge, skills, attitudes and values; c) facilitating interdisciplinary knowledge for understanding and solving complex business and engineering problems; d) enhancing students’ intellectual maturity and critical thinking to act in responsible ways, coping with new realities and demands. Finally, the authors shared their views on the need to provide tailored content and quality information with differentiated knowledge about topics from different areas which might induce transformational change in local curricula to foster a sustainable mindset of graduates.